Corporate business valuation for mergers and acquisitions - Aluko, Bioye Tajudeen; Amidu, Abdul‐Rasheed (International Journal of Strategic Property Management, 2010)
Business combinations including mergers and acquisitions are important features of corporate structural changes. The Investments Securities Acts (ISA), 1999 charge the Securities and Exchange Commission with the responsibility to review and approve all business combinations in Nigeria. And, real property is an integral factor in many of such strategic business decisions and, need to be set in a business context. This paper, therefore, examines how corporate business entities are and could be valued for mergers and acquisitions through exploratory research. It also explains the relevance of goodwill, marriage value, and fair value concept in corporate business asset valuation. The paper found out inter‐ alia that the value of holding property to the business needs to be measured against the return that the equity could achieve both within the business and elsewhere. It also, prima facie, shows that the role of the valuer is not one of accountant but interpreter of financial and physical information with a clear understanding of the nature of the business under consideration in merger and acquisition.First Published online: 18 Oct 2010